2019
DOI: 10.3390/f10110971
|View full text |Cite
|
Sign up to set email alerts
|

Time-Lag Effect Between Sap Flow and Environmental Factors of Larix principis-rupprechtii Mayr

Abstract: A time lag between sap flux density (Js) and meteorological factors has been widely reported, but the controlling factors of the time lag are poorly understood. To interpret the time lag phenomenon systematically, thermal dissipation probes were placed into each of eight trees to measure the Js of Larix principis-rupprechtii Mayr. in the Liupan Mountains in Northwest China. Meteorological factors, including vapor pressure deficit (VPD), solar radiation (Rs) and air temperature (Ta), were synchronously measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Shen et al [13] reported that the sap flow of the Populus gansuensis linearly increased with R s , and logarithmically increased with VPD and T. All these studies indicate that the response of transpiration to environmental variables is climateand ecosystem-specific and more research is required to better understand environmental control on transpiration. In addition, diurnal hysteresis between transpiration and environmental variables has been reported in different ecosystems [14][15][16][17]. Both transpiration and environmental variables exhibit diurnal changes, reaching peaks at different times and resulting in a hysteresis behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [13] reported that the sap flow of the Populus gansuensis linearly increased with R s , and logarithmically increased with VPD and T. All these studies indicate that the response of transpiration to environmental variables is climateand ecosystem-specific and more research is required to better understand environmental control on transpiration. In addition, diurnal hysteresis between transpiration and environmental variables has been reported in different ecosystems [14][15][16][17]. Both transpiration and environmental variables exhibit diurnal changes, reaching peaks at different times and resulting in a hysteresis behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This shows a close relationship between ET ref and T. Different from the ET ref and LAI, the influence of the soil water supply capacity on T is usually reflected in limitations to T due to water stress [24]. Studies in the semi-humid regions of Northwest China have shown that when RSWC is less than 0.38, coniferous forests will be under drought stress and the restriction of RSWC will result in losses in T of up to 11.6% [7,25]. Previous investigations also indicated that canopy T was affected by the coupling of leaves, atmosphere, and soil moisture; thus, ET ref , RSWC, and LAI should be included when investigating the T response mechanisms.…”
Section: Introductionmentioning
confidence: 94%
“…Plant transpiration is conducted via stomatal processes and the hysteresis between environmental factors and the SSF can be regarded as the adaptation of plants to environmental factors caused by water limitation (Matheny et al, 2014;Ma et al, 2017;Zha et al, 2017;Hong et al, 2019;Wang et al, 2019). Our results show that the daily cycle for PAR, Ta, and VPD (24 h) lags behind that for the SSF (Figure 6), which is in agreement with previous studies (Ma et al, 2017;Hong et al, 2019;Wang et al, 2019). Generally, the maximum PAR occurs at noon, while the maximum temperature and the maximum VPD usually appear in the afternoon.…”
Section: Influence Of Environmental Factors On the Stem Sap Flowmentioning
confidence: 99%